2002
DOI: 10.1051/vetres:2001008
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous mycotoxic nephropathy in Bulgarian chickens with unclarified mycotoxin aetiology

Abstract: -Histopathological, biochemical and toxicological investigations of tissues and blood of normally slaughtered chickens exhibiting different frequencies (1-2%, 40-50% and above 80%) of nephropathy changes (congested or pale and enlarged kidneys) at the slaughtering meat inspection were carried out to elucidate the aetiology of nephropathies of chickens encountered in Bulgaria. A close relationship was observed between the frequency of this nephropathy and the rate of nephrotoxic mycotoxin ochratoxin A in muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
55
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 20 publications
11
55
0
2
Order By: Relevance
“…However, there has been a study that described a decrease in the body weights of progeny chicks obtained from breeder hens kept on OTA-contaminated rations (Choudhury et al, 1971). A decrease in the weight of immunological organs due to OTA feeding has been reported in broiler chicks (Singh et al, 1990;Stoev et al, 2002). It is possible that the noted decreases in the weights of immunological organs in this study are due to cytotoxic/necrotic effects of OTA residues in the eggs (data not shown) acting, in part, upon the developing organs of the chicks.…”
Section: Discussionmentioning
confidence: 47%
“…However, there has been a study that described a decrease in the body weights of progeny chicks obtained from breeder hens kept on OTA-contaminated rations (Choudhury et al, 1971). A decrease in the weight of immunological organs due to OTA feeding has been reported in broiler chicks (Singh et al, 1990;Stoev et al, 2002). It is possible that the noted decreases in the weights of immunological organs in this study are due to cytotoxic/necrotic effects of OTA residues in the eggs (data not shown) acting, in part, upon the developing organs of the chicks.…”
Section: Discussionmentioning
confidence: 47%
“…Unfortunately, the literature is lacking information about the effect of in ovo OTA on the body and relative organ weights of developing chicks. However, studies made on OTA-fed chicks reported an increase in the weights of liver and kidneys (Hanif et al 2008;Stoev et al 2002) and a decrease in weights of bursa of Fabricius (Singh et al 1990;Gibson et al 1989). This increase in the weights of liver and kidneys is correlated with nephro-and hepatotoxic effects of OTA, resulting in the accumulation of inflammatory cells (Zahoor-ul-Hassan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Penicillic acid (PA) is another mycotoxin produced by P. aurantiogriseum strains and some other fungi such as those of the Aspergillus ochraceus group, which are the major producers of OTA in the warmer climatic zones (Stoev et al 1998a;Stoev 2008a). The same mycotoxin was found to be also involved in mycotoxic nephropathy in animals (Stoev et al 2001(Stoev et al , 2002a. CIT is usually produced by P. citrinum, which can also be considered as a storage fungus.…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery, the disease has been named in different ways: nephrosis provoked by moulds, chronic interstitial fibrosis of kidneys, chronic interstitial nephritis, ochratoxicosis, mycotoxic nephropathy, etc. Some varieties were found with the manifestation of the disease, especially with the clinicomorphological picture, which in many cases is influenced by the combined nephrotoxic effect of several nephrotoxic mycotoxins (Stoev et al 1998a(Stoev et al , 2001(Stoev et al , 2002aStoev 2008b) as well as by some secondary bacterial infections as a result of pronounced immunosuppression in the affected animals (Stoev et al 2000a, b;Oswald et al 2003Oswald et al , 2005.…”
Section: Introductionmentioning
confidence: 99%